MAGNESIUM DEFICIENCY IN PATHOGENESIS OF CARDIOVASCULAR DISEASES: RECENT DEVELOPMENTS - D. E. Maylian; V. V. Kolomiets (Российский кардиологический журнал)
The review focuses on the influence of magnesium deficiency on a variety of cardiovascular pathogenetic chains. The issues especially considered are vessel tone regulation, endothelial function, atherogenesis and atherothrombosis, as the functioning of cardiac conduction system. These mechanisms, disordered, lead to initiation and progression of the disorders as essential hypertension, chronic heart failure and coronary heart disease. Also, the data systematized, on the role of magnesium homeostasis correction for prevention and treatment of these pathologies.